Teneurin C‐Terminal Associated Peptide (TCAP)‐1 Attenuates Restraint Stress‐Induced Corticosterone Increases in Male Mice and Rats - Lauren E. Mueller; Roseanne S. Wexler; David A. Lovejoy; Robert B. Stein; Andrew M. Slee (Pharmacology Research & Perspectives)
ABSTRACT Hyperactivation of the hypothalamic‐pituitary‐adrenal (HPA) axis response can result in anxiety and other neuropsychiatric disorders and effective therapeutics are needed to mitigate this maladaptive response. Here we examined the effects of Teneurin C‐terminal Associated Peptide (TCAP)‐1, a peptide known to inhibit corticotropin releasing factor (CRF)‐mediated stress, on the physiological expression of stress, and whether the effects of TCAP‐1 were dependent on the route of administration. We first examined whether subcutaneous administration of TCAP‐1 influenced tube restraint stress‐induced corticosterone (CORT) increases in both male mice and rats. Using a similar model, we further examined the efficacy and time course of intranasal TCAP‐1. Results showed that subcutaneous TCAP‐1 administration attenuated the expression of the physiological manifestation of stress in male mice and rats, and that intranasal TCAP‐1 delivered prophylactically is effective at attenuating stress‐induced CORT increases in male rats. These data indicate that TCAP‐1 delivered though non‐invasive routes of administration could have potential as a clinically relevant anxiolytic.